Environmental Governance: Urban Waste Management Model - Horaphat Narethong (Newinera Publisher, 2020)
Waste management that is not good will also have a negative impact on the environment, public health, and this certainly has wider implications such as environmental pollution. This article outlines environmental governance in the waste management process and a model of good urban waste management. Environmental governance is important in understanding the issue of waste management which is a complex environmental issue in urban areas. A good model for waste management is with the unit paying attention to sewage, leachate water treatment, and combustion of methane / flare gas access. The model described as integrated management is widely applied in big cities. The integrated waste management process is carried out by implementing preventive measures and reuse efforts with the aim that the waste does not form.